PERMASALAHAN FUNDAMENTAL PIDANA MATI TERHADAP TINDAK PIDANA KORUPSI - Prasetyo Budi Wicaksana (AMERTA Jurnal Ilmiah Ilmu Sosial dan Humaniora, 2023)
Corruption is an extra ordinary crime which is very detrimental to the Indonesian nation and state. For this reason, the Government has issued or made a law, namely Law number 31 of 1999 in conjunction with Law number 20 of 2001 concerning the Eradication of Corruption Crimes. That in article 2 paragraph 2 of the Law it is said that the death penalty can be applied if Indonesia is in certain circumstances. This particular situation means if Indonesia is in a state of disaster emergency, a state of war or a disaster emergency. However, the problem that often arises is that a prosecutor does not dare to enforce the charges under Article 2, paragraph 2 of the Corruption Eradication Law. Keywords: corruption Tindak Pidana Korupsi merupakan suatu tindak pidana extra ordinary crime yang sangat merugikan bangsa dan negara Indonesia. Untuk itu Pemerintah telah menerbitkan atau membuat suatu Undang-Undang yaitu Undang-Undang nomor 31 tahun 1999 jo Undang-Undang nomor 20 tahun 2001 mengenai Pemberantasan Tindak Pidana Korupsi. Bahwa di dalam pasal 2 ayat 2 Undang-Undang tersebut dikatakan bahwa Pidana Mati dapat diterapkan bila Indonesia dalam keadaan tertentu. Keadaan tertentu tersebut maksudnya apabila Indonesia dalam keadaan darurat bencana, keadaan perang atau darurat bencana. Akan tetapi permasalahan yang sering muncul yaitu tidak beraninya seorang jaksa memaksukan dakwaan pasal 2 ayat 2 Undang-undang Pemberantasan Tindak Pidana Korupsi. Kata kunci: korupsi